EKV Model Based Analog/RF CMOS Design Pre-SPICE Tool - Gholamreza Khademevatan; ali jalali (Iranian journal of electrical & electronic engineering, 2025)
A novel simplified EKV model base analog/RF CMOS design pre-SPICE tool is presented in this paper. Addition to facilitating the sizing process, this CAD tool can also optimize circuit characteristics. By having a web address, users can access it without installing any software. Using a graphical and a numerical view, the designer can select degrees of freedom and observe the MOS circuit performance. Through the use of charts versus IC, the graphical view can show tradeoffs in circuit performance in real-time. Charts can be displayed simultaneously in both linear and logarithmic scales. IC CRIT , is also available and can be displayed on the charts. This tool is not limited to one process and it is possible to select different processes. It is efficient for pre-SPICE designs, enhancing intuitive understanding and the designer's experience for future projects while eliminating the need for trial-and-error simulations. Furthermore, the predicted results align well with simulation outcomes, demonstrating the effectiveness of the design and optimization method presented. Two methodologies for selecting optimum ICs are presented by this tool. These are illustrated by the study of linearity indices, AIP3 and IIP3, in one-stage and two-stage differential amplifiers and the design of a single-ended OTA.